In Vitro Differentiation of First Trimester Human Umbilical Cord Perivascular Cells into Contracting Cardiomyocyte-Like Cells - Peter Szaraz; Matthew Librach; Leila Maghen; Farwah Iqbal; Tanya A. Barretto; Shlomit Kenigsberg; Andrée Gauthier-Fisher; Clifford L. Librach (Hindawi Limited, 2016)
Myocardial infarction (MI) causes an extensive loss of heart muscle cells and leads to congestive heart disease (CAD), the leading cause of mortality and morbidity worldwide. Mesenchymal stromal cell- (MSC-) based cell therapy is a promising option to replace invasive interventions. However the optimal cell type providing significant cardiac regeneration after MI is yet to be found. The aim of our study was to investigate the cardiomyogenic differentiation potential of first trimester human umbilical cord perivascular cells (FTM HUCPVCs), a novel, young source of immunoprivileged mesenchymal stromal cells. Based on the expression of cardiomyocyte markers (cTnT, MYH6, SIRPA, and CX43) FTM and term HUCPVCs achieved significantly increased cardiomyogenic differentiation compared to bone marrow MSCs, while their immunogenicity remained significantly lower as indicated by HLA-A and HLA-G expression and susceptibility to T cell mediated cytotoxicity. When applying aggregate-based differentiation, FTM HUCPVCs showed increased aggregate formation potential and generated contracting cells within 1 week of coculture, making them the first MSC type with this ability. Our results indicate that young FTM HUCPVCs have superior cardiomyogenic potential coupled with beneficial immunogenic properties when compared to MSCs of older tissue sources, suggesting that in vitro predifferentiation could be a potential strategy to increase their effectiveness in vivo.